2014
DOI: 10.1371/journal.pone.0093641
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Improves the Quality of In Vitro Produced (IVP) Bovine Embryos: Implications for Blastocyst Development, Cryotolerance, and Modifications of Relevant Gene Expression

Abstract: To evaluate the potential effects of melatonin on the kinetics of embryo development and quality of blastocyst during the process of in vitro bovine embryo culture. Bovine cumulus–oocyte complexes (COCs) were fertilized after in vitro maturation. The presumed zygotes were cultured in in vitro culture medium supplemented with or without 10−7 M melatonin. The cleavage rate, 8-cell rate and blastocyst rate were examined to identify the kinetics of embryo development. The hatched blastocyst rate, mortality rate af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 55 publications
6
48
1
3
Order By: Relevance
“…Our data indicates that a relative high level of melatonin (10 −3 mol/L) significantly reversed the reduction in blastocyst quality caused by AFB1 exposure during oocyte maturation. Similarly, previous studies also proved that melatonin has an essential function in improving embryo quality under normal IVM‐IVF conditions or stressed conditions …”
Section: Discussionmentioning
confidence: 55%
“…Our data indicates that a relative high level of melatonin (10 −3 mol/L) significantly reversed the reduction in blastocyst quality caused by AFB1 exposure during oocyte maturation. Similarly, previous studies also proved that melatonin has an essential function in improving embryo quality under normal IVM‐IVF conditions or stressed conditions …”
Section: Discussionmentioning
confidence: 55%
“…Based on promising results for melatonin in previous work using testicular tissue of CD-1 mice4 and rats,20 we hypothesized its positive effect in our murine testicular organ cultures. The concentration of melatonin we used was 10 −7  M, which was used previously to produce the antioxidant effect 4,26,36,37…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the embryo quality and viability is mainly affected by in vitro culture conditions [4, 22,23,24], and high-quality embryos can be achieved through modifying culture conditions [24, 25]. Baicalin has been reported to promote embryo implantation and maintain pregnancy in mice [13].…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism behind baicalin-induced up-regulation of Dnmt3a gene expression is unclear, higher Dnmt3a mRNA levels in mouse blastocyst than its early developmental stage to establish a new embryonic methylation pattern have been reported [47]. Moreover, the beneficial effects of melatonin on bovine embryo-quality have also been shown to be due to the increased DNMT3a gene expression [25]. Our study indicates that baicalin enhances developmental competence of mouse embryos in vitro via down-regulating Dnmt1 and up-regulating Dnmt3a gene expressions to improve DNA methylation.…”
Section: Discussionmentioning
confidence: 99%